The Role of Ecological and Digital Leadership in Improving School Performance - Fitriana, Nita; Zuraida, Lukia (Indonesian Journal Publisher, 2025)
The advancement of technology and environmental issues has become a major challenge in the education sector. Schools are required to adopt digital transformation while simultaneously implementing sustainability principles. This study analyzes the role of ecological leadership and digital leadership in improving the performance of Sekolah Cendekia BAZNAS (SCB). This research employs a qualitative case study approach, collecting data through observations, in-depth interviews, and document analysis. The findings reveal that ecological leadership at SCB is manifested in environmental policies, innovative programs such as the